HUBUNGAN TEKNIK RELAKSASI BERNAFAS DENGA RESPON ADAPTASI NYERI PADA PASIEN INPARTU KALA I DI PUSKESMAS KETAPANG II SAMPIT TAHUN 2018 - agus mulyadi (Jurnal Ilmiah Kebidanan dan Kesehatan Wanita, 2019)
ABSTRACT Background: Relaxation Technique is a pain reliever technique that gives the biggest input because relaxation technique in labor can prevent excessive post partum errors. Every year more than 200 million pregnant women, most pregnancies end with live births to healthy mothers nevertheless, in some cases birth is not a happening event but becomes a painful period of pain, fear, suffering and even death. Objective: To know the relation of relaxation breathing technique with the response of adaptation pain in the maternal mother Inpartu kala I in Ketapang II Sampit Community Health Center 2018. Research Method: This research is include in qualitative research with Design used is Cross sectional which use observation and interview test where the measurement of dependent and Independen is done stimulationeously that is directly.Researcher set sample in this research is equal to 35 sample. This study used a checklist instrumen that was distributed to the delivery mothers Inpartu kala I. The location of the research was conducted at the Puskesmas Ketapang II. Results: Based on the resulth of the research, it can be known that patient Adaptation Response which has Breathing relaxation technique, the majority get response of pain adaptation by 30 respondents (100%) and from 5 respondents who do not use Relaxation techniques breathe majority get response of pain adaptation 5 respondent (62,5%). After the statitistical test with chi-square test, chi-square value (19,688) and p-value 0,00 which means that there is a relationship between breath relaxation technique with Patient Adaptation Response in Maternal Woman Inpartu kala I. Conclusion: Maternal mothers respond to pain in different ways. Some mothers may feel fearful and axious while others are tolerant and optimistic. Tired women experience the energy and ability to use strategies such as dstraction and imagination to deal with pain.